Ambiguity in the Definition: The Need for Caution in Prosecuting Persons Under the Anti-pornography Act. (23rd November 2018) - Doya, Nanima Robert
Abstract: The purpose of Parliamentary scrutiny and debates in drafting a law is to avoid ambiguity, vagueness and definitional deficiencies. The penal provisions in the criminal laws should be clear on the acts that constitute the offence, and the intention of the accused person. A look at the drafting history of a law may aid one to ascertain the intention of Parliament. It is argued that there are challenges to the implementation of the Anti-pornography Act from an interpretational perspective. This contribution critiques the role of Parliament in defining pornography in the process of enacting the Anti-pornography Act. The possible challenges to prosecution that arise from this role are identified. Recommendations on the drafting process follow.